Iodized Salt Use and Salt Iodine Content among Household Salts from SDistricts of Eastern Nepal - Khatiwada, S; Gelal, B; Tamang, M K; KC, R (Journal of Nepal Health Research Council, 2015)
Background: Universal salt iodization is considered the best strategy for controlling iodine deficiency disorders in Nepal. This study was done to find iodized salt use among Nepalese population and the iodine content of household salts. Methods: Six districts (Siraha, Saptari, Jhapa, Udayapur, Ilam and Panchthar) were chosen randomly from 16 districts of eastern Nepal for the study. In each district, three schools (private and government) were chosen randomly for sample collection. A total of 1803 salt samples were collected from schools of those districts. For sample collection a clean air tight plastic pouch was provided to each school child and was asked to bring approximately 15 gm of their kitchen salt. The information about type of salt used; ‘two child logo’ iodized salt or crystal salt was obtained from each child and salt iodine content was estimated using iodometric titration. Results: At the time of study, 85% (n=1533) of Nepalese households were found to use iodized salt whereas 15% (n=270) used crystal salt. The mean iodine content in iodized and crystal salt was 40.8±12.35 ppm and 18.43±11.49ppm respectively. There was significant difference between iodized and crystal salts use and salt iodine content of iodized and crystal salt among different districts (p value <0.001 at confidence level of 95%). Of the total samples, only 169 samples (9.4% of samples) have iodine content<15 ppm. Conclusions: Most Nepalese households have access to iodized salt most salt samples have sufficient iodine content. Keywords: Iodine deficiency; Nepal; salt iodine content.